Rebranding Opak Gambir Cahaya Kita Sebagai Upaya Meningkatkan Brand Awareness - Mochammad Rayyan Thalib; Ayundha Evanthi (STIPAS Tahasak Danum Pambelum Keuskupan Palangkaraya, 2023)
Assistance in community service programs with an entrepreneurial and creative economy scheme by the East Java National